Ekaningrum , Yuniawati PENGARUH MOTIVASI TERHADAP PRESTASI BELAJAR DI POLITEKNIK NSC (STUDI KASUS : MAHASISWA YANG BEKERJA & YANG BELUM BEKERJA) (Nsc Press, 2014)
Purpose and targets of the study - This study aims to determine the exact influence student motivation to work and that has not worked on learning achievement at the Polytechnic of Surabaya . Methodology - This research done using Analysis Techniques relianilitas test validity and statistical analysis is then used multiple linear regression , the coefficient of multiple determination , and F-test , the data required in this study were only scattered questionnaire for students who work or not work . In this study the sample size was determined by the investigators as much as 144. Into consideration in the determination of this sample , the NSC is all student Polytechnic of Surabaya , which consists of four (4 ) courses , ( Hospitality , Accounting , Business Administration and ComputerEngineeringforce in 2012 , 2011 , and 2010 . Outcomes research - In this study the expected target is 1 ) to determine the motivation of students who work and who have not been working on learning achievement each semester so that progress can be monitored until the time of completing the study on the Diploma program . 2 ) To provide input to the proposed scientific journal.